KURIKULUM SENI BUDAYA DI SMP NEGERI 5 LUBUK ALUNG: STUDI KASUS PENERAPAN KTSP - Peniyanti Peniyanti; Idawati Syarif; Esy Maestro (SENDRATASIK UNP, 2013)
Abstract The article aimed at explaining and revealing the implementation of School-Based Curriculum in the learning of arts at SMP Negeri 5 Lubuk Alung. The design of the research was descriptive qualitative. The data obtained from observation, interview, and library research. The data was analyzed using phenomenology technique. The research resulted that the implementation of School-Based Curriculum was not as how it was expected. It is due to the fact that teachers did not understand the learning material so that what was in the lesson plan did not suit the material. Moreover, the teacher did not have musical arts education background. Thus, it effects on wrong way of implementation.